2010
DOI: 10.1002/yea.1764
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic catastrophe induced by overexpression of budding yeast Rad2p

Abstract: Mitotic catastrophe provokes endopolyploidy, giant cell formation and, eventually, delayed cell death. Mitotic catastrophe is induced by defective cell cycle checkpoints and by some anticancer drugs, ionizing radiation and microtubule-destabilizing agents. RAD2 is a yeast homologue of XPG, which is a human endonuclease involved in nucleotide excision repair. Here we show that Rad2p overexpression alone, in the absence of extrinsic DNA damage, causes cell growth arrest and mitotic catastrophe. Interestingly, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…As observed by the growth patterns on plates 26 , Rad2p over-expression completely inhibited cell growth for up to 40 hours in liquid medium ( Figure 1A). However, Rad2p-expressing cells resumed growth after 40 hours of induction and eventually reached a stationary stage similar to the vector control indicating that some of the cells escaped from growth arrest and regained the ability to duplicate.…”
Section: Growth Of Rad2p-induced Cell Growth Arrested Cellsmentioning
confidence: 82%
See 4 more Smart Citations
“…As observed by the growth patterns on plates 26 , Rad2p over-expression completely inhibited cell growth for up to 40 hours in liquid medium ( Figure 1A). However, Rad2p-expressing cells resumed growth after 40 hours of induction and eventually reached a stationary stage similar to the vector control indicating that some of the cells escaped from growth arrest and regained the ability to duplicate.…”
Section: Growth Of Rad2p-induced Cell Growth Arrested Cellsmentioning
confidence: 82%
“…Furthermore, Rad2p-induced cells displayed a morphology characteristic of mitotic catastrophe, and a significant portion of the cell population contained ¤2-fold the normal DNA content 26 . On the other hand, we observed that cells growth-arrested by Rad2p resumed growth after a prolonged incubation in galactose liquid medium, indicating that some cells experiencing Rad2p-induced mitotic catastrophe resumed cell growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations